The Importance of Project-Based Learning in Student Entrepreneurship Edecation - Muhammad Ade Kurnia Harahap (Indo-MathEdu Intellectuals Journal, 2023)
Education is one of the main pillars in the development of a country and has an important role in creating competent and qualified human resources. Currently, the main challenge in education is to prepare students to face the world of work that continues to grow and change rapidly. This research aims to examine the importance of project-based learning in students' entrepreneurship education. This research is a literature review that uses a qualitative method approach, which means it will analyse and interpret data by relying on information and text from various sources. The study results show that project-based learning has a crucial role in students' entrepreneurship education. By providing practical experience, building practical skills, developing critical and creative thinking abilities, and stimulating creativity and initiative, this method prepares students to face the dynamic and competitive business world. In addition, project-based learning strengthens the connection between the university and the business world, enables students to understand current market dynamics, and strengthens their social and communication skills. The limitation of this study lies in the method as it relies on the availability of relevant sources, which could make it less comprehensive.